Analisis Faktor Risiko KLB Hepatitis A di Pondok Pesantren X Kabupaten Rokan Hilir Provinsi Riau - Mardani, Said; Helda; Rajunitrigo; Muryanto, Irwan (Jurnal Kesehatan Komunitas, 2024)
In January 2023, an outbreak of Hepatitis A occurred at Islamic Boarding School (IBS) X, Rokan Hilir Regency, which infected many students. This study aims to identify the risk factors for hepatitis A outbreaks. This study uses a case-control design with a ratio of 1:1. Total sample is 232 (116 samples per group). The research population was all students and residents of IBS X. Cases were people who have clinical criteria for hepatitis A according to the doctor's diagnosis. Controls were people who did not experience clinical symptoms of hepatitis A, selected using a consecutive sampling method with matching by age and sex. Data were analyzed univariate, bivariate using a chi-square test, and multivariate using a conditional logistic regression test. This study found that the index case started to feel symptoms on October 20, 2022. The epidemic curve shows a continuous common source pattern. The final model of the regression logistic test obtained two significant variables, namely contact history (OR=9.92, 95% CI: 3.31-29.72, p=<0.001) and unclean nail conditions (OR=4.64, 95% CI: 1.55-13.87, p=0.006). This study concluded that the risk factors for hepatitis A outbreaks at IBS X were contact history and unclean nail conditions. We recommend isolating cases to prevent transmission through contact from cases to healthy people as well as providing adequate facilities for washing hands with soap and increasing education about healthy behavior to maintain good nail cleanliness and personal hygiene conditions for all students and residents of IBS X.